Critical relaxation and the combined effects of spatial and temporal boundaries - Marcuzzi, M.; Gambassi, A. (Condensed Matter Physics, 2014)
We revisit here the problem of the collective non-equilibrium dynamics of a classical statistical system at a critical point and in the presence of surfaces. The effects of breaking separately space- and time-translational invariance are well understood, hence we focus here on the emergence of a non-trivial interplay between them. For this purpose, we consider a semi-infinite model with O(n)-symmetry and purely dissipative dynamics which is prepared in a disordered state and then suddenly quenched to its critical temperature. We determine the short-distance behaviour of its response function within a perturbative approach which does not rely on any a priori assumption on the scaling form of this quantity. Ми знову розглядаємо проблему колективної нерiвноважної динамiки класичної статистичної системи
в критичнiй точцi i в присутностi поверхонь. Вплив порушення порiзно просторової i часової трансляцiйної iнварiантностi є добре зрозумiлим, тому тут ми зосереджуємо увагу на виникненнi нетривiальної
взаємодiї мiж ними. Для цiєї мети ми розглядаємо напiвбезмежну модель з O(n)-симетрiєю i цiлковито дисипативну динамiку, пiдготовану в невпорядкованому станi, i потiм раптово заморожену до своєї
критичної температури. Ми визначаємо поведiнку її функцiї вiдгуку на коротких вiдстанях в межах теорiї
збурень, не спираючись на жодне припущення щодо форми цiєї величини.